2005
DOI: 10.1007/s10534-005-0335-3
|View full text |Cite
|
Sign up to set email alerts
|

Metal accumulation and apoptosis in the alimentary canal of Lumbricus terrestris as a metal biomarker

Abstract: The chloragogenous tissue and the intestinal epithelium of adult earthworms, Lumbricus terrestris, sampled from sites with and without volcanic activity in the Azores were submitted to hematoxylin/eosin staining, autometallography and TUNEL-test in order to quantify the radial thickness of both tissues, their relative abundance of metals and apoptosis levels. Metals were visualized, through light microscopy, as black silver deposits (BSD) mostly in the chloragogenous tissue. The lowest radial thickness values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In agreement with this effect, it has been found that a variety of environmental organic and inorganic chemical stressors can cause changes in the chloragocytes (Fischer and Molnar, 1992;Vogel and Seifert, 1992). Amaral and Rodrigues (2005) found higher apoptotic rates of the cells of the chloragogenous tissue and intestinal epithelium in Furnas. Since this is possibly related to higher Zn and Cd bioavailability it may explain the lower values of RTC and RTIE found in this volcanically active area.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In agreement with this effect, it has been found that a variety of environmental organic and inorganic chemical stressors can cause changes in the chloragocytes (Fischer and Molnar, 1992;Vogel and Seifert, 1992). Amaral and Rodrigues (2005) found higher apoptotic rates of the cells of the chloragogenous tissue and intestinal epithelium in Furnas. Since this is possibly related to higher Zn and Cd bioavailability it may explain the lower values of RTC and RTIE found in this volcanically active area.…”
Section: Discussionmentioning
confidence: 54%
“…In a previous study where BSD extents were quantified, earthworms from Furnas exhibited a higher BSD extent than those from Santa Maria (Amaral and Rodrigues, 2005).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Bearing this in mind, and since it is known that metals can promote and originate changes in the composition and diameter of digestive epithelia of several invertebrates that can be measured through variations in the mean radial epithelial thickness (Amaral et al, 2006a;Marigomez et al, 2006;Cunha et al, 2008), but also with apoptosis, another cellular response that may be triggered by metal stress. Apoptosis is involved in cell turnover, and has been suggested as a biomarker of the effect of bioavailable metals when its rates vary from normal (Amaral and Rodrigues, 2005;Cunha et al, 2008). The present study aimed to determine whether larvae exposed and not exposed to volcanic activity show distinct metal body burdens, but also to analyze the effects of such metals on the midgut cell morphometry and apoptosis.…”
Section: S C I E N C E O F T H E T O T a L E N V I R O N M E N Tmentioning
confidence: 99%
“…Consequently, organisms living in such environment may be continually exposed to metals, either as particles or associated with gases (Hansell et al, 2006). The association between changes in the digestive epithelium and the occurrence of apoptosis under chronic metal and metalloid exposure, originated by volcanic activity, has been previously found in terrestrial (e.g., earthworms, and snails) and marine invertebrates (e.g., limpets) (Amaral and Rodrigues, 2005;Zaldibar et al, 2006;Cunha et al, 2008). Thus, it is important to look for organisms that can be used as biological indicators or sentinels for the presence of those pollutants under such conditions, and in which one can rapidly measure several biomarkers of exposure and/or effects.…”
mentioning
confidence: 99%